Breath by Breath: Reconsidering the Project of Critical Pedagogy Through the Lens of Zen Buddhist Thought and Practice. (October 2019) - Holohan, Kevin
This article examines how Zen Buddhism conceives of human suffering, the causes of suffering, and the method by which human suffering can be alleviated and compares these with similar notions within critical social theory and its educational manifestation in the critical pedagogy movement. While both Zen Buddhist and critical theories/discourses aim to uncover the roots of human suffering and offer particular methods to help alleviate it, these systems of thought differ in fundamental ways. Consideration of significant concepts within Buddhist thought and practice can address some of the criticisms that have been leveled against the foundations and project of critical pedagogy. Ultimately, the article illustrates how a Zen Buddhist–oriented critical pedagogy based upon notions of interdependence, impermanence, and "no-self" can be a more humane, inclusive, relevant, and applicable approach to working toward a more just and equitable social order.